2009
DOI: 10.3168/jds.2009-2351
|View full text |Cite
|
Sign up to set email alerts
|

Net flux of nutrients across the rumen wall of lactating dairy cows as influenced by dietary supplements of folic acid

Abstract: The objective of the present study was to determine whether a dietary supplementation of folic acid, at levels used in our previous studies, would affect ruminal fermentation and the net flux of nutrients across the rumen wall of lactating dairy cows. Approximately 4 wk after calving, 5 lactating multiparous cows were surgically equipped with a ruminal cannula, an ultrasonic flow probe around the right ruminal artery, and indwelling catheters in the right ruminal vein and the ileocolic artery. Cows were fed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
2
22
1
Order By: Relevance
“…The reason for the increased CP degradability failing to result in the increased ammonia N content was attributed to the increased synthesis of microbial protein demonstrated by the increased urinary PD excretion. The results were in agreement with the finding of Wejdemar (1996) where the addition of folic acid to clarified ruminal fluid promoted the growth of B. fibrisolvens TC33 and its utilization of ammonia N. Nevertheless, Girard et al (2009) reported that the uptake of urea N by the rumen wall tended to increase quadratically when lactating multiparous cows supplied folic acid daily at 0, 3, or 6 mg/kg BW.…”
Section: Ruminal Fermentationsupporting
confidence: 92%
See 4 more Smart Citations
“…The reason for the increased CP degradability failing to result in the increased ammonia N content was attributed to the increased synthesis of microbial protein demonstrated by the increased urinary PD excretion. The results were in agreement with the finding of Wejdemar (1996) where the addition of folic acid to clarified ruminal fluid promoted the growth of B. fibrisolvens TC33 and its utilization of ammonia N. Nevertheless, Girard et al (2009) reported that the uptake of urea N by the rumen wall tended to increase quadratically when lactating multiparous cows supplied folic acid daily at 0, 3, or 6 mg/kg BW.…”
Section: Ruminal Fermentationsupporting
confidence: 92%
“…Although in the current study the supplementary RPFA which contained 100 g/kg of folic acid and its ruminal degradability was 0.304, could provide 18.2, 36.4 and 54.6 mg/d of folic acid for ruminal microorganism in LRPFA, MRPFA and HRPFA group, respectively, the level of folic acid released into the rumen was lower than that of in Chiquette et al (1993), Girard et al (1994) and Girard et al (2009). The positive effects of supplementary RPFA on ruminal fermentation may have resulted from a combined action of the low CP and energy diets, lower passage rate through the rumen, ruminal degradable folic acid and its protection material.…”
Section: Ruminal Fermentationcontrasting
confidence: 52%
See 3 more Smart Citations